Specificities of Spatial System Transformation and Strategies of the Russian Arctic Redevelopment under the Conditions of Climate Changes - Leksin, Vladimir Nikolaevich; Porfiryev, Boris Nikolaevich (Economy of Regions, 2017)
A bunch of papers has been published by foreign and Russian researchers on climate change impact on the environment and regional socioeconomic development. The bulk of them is focused on analyzing drivers and impact assessments for the Arctic region characterized by the most intensive climate change worldwide. The paper puts to the fore a nontrivial issue of considering the climate change impact factor within the methodology and practice of the strategic process of the Russian Arctic redevelopment. The issue above is complicated by the imperative of ranking of the salience of the climate change socioeconomic implications as priorities of the governance and public administration of the comprehensive development of the macro-region under consideration. The lack of the effective tools for consolidation of the needed resources further exacerbates it. The summary of the findings of the national and international researchers in the area of climate change impact on environment, settlements and economic activity in the Arctic Zone of the Russian Federation (AZRF) is introduced to substantiate the policy decisions made. We have specified the methodological issues related to peculiarities and role of the climate change factor plays in policy decisions within the context of contemporary knowledge on patterns of spatial systems transformation, their capabilities of selforganization and adaptation to externalities. The authors have revealed the general regularities and specificity of the AZRF transformation as a spatial system and the impact of climate change produced on this process. We have particularly emphasized the issues of adaptation to climate change of the AZRF indigenous population whose health and economic activities experience increased risks associated with high intensiveness of the climatic fluctuations. Recommendations for using scenario (variation) approach to redesigning strategies and programs of AZRF development are substantiated.